2020
DOI: 10.1098/rsta.2019.0321
|View full text |Cite
|
Sign up to set email alerts
|

Using epidemiology to estimate the impact and burden of exposure to air pollutants

Abstract: This paper focuses on the use of results of epidemiological studies to quantify the effects on health, particularly on mortality, of long-term exposure to air pollutants. It introduces health impact assessment methods, used to predict the benefits that can be expected from implementation of interventions to reduce emissions of pollutants. It also explains the estimation of annual mortality burdens attributable to current levels of pollution. Burden estimates are intended to meet the need to communicate the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…An increasing number of studies, using satellite and ground data, reported reductions in the concentrations and emissions of air pollutants across the world [4]. Considering the health problems caused by exposure to air pollutants [5][6][7][8][9], the reductions in pollutant levels offer an opportunity to rethink pollution control strategies since an estimated 50,000 pollution-related deaths were avoided during the lockdown [10]. Kumari and Toshniwal [11] in their study of 12 cities and over 150 air quality monitoring stations (AQMS), highlighted the reductions in air pollutant concentrations (PM 2.5 , PM 10 and NO 2 ) varying from 20 to 64%.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies, using satellite and ground data, reported reductions in the concentrations and emissions of air pollutants across the world [4]. Considering the health problems caused by exposure to air pollutants [5][6][7][8][9], the reductions in pollutant levels offer an opportunity to rethink pollution control strategies since an estimated 50,000 pollution-related deaths were avoided during the lockdown [10]. Kumari and Toshniwal [11] in their study of 12 cities and over 150 air quality monitoring stations (AQMS), highlighted the reductions in air pollutant concentrations (PM 2.5 , PM 10 and NO 2 ) varying from 20 to 64%.…”
Section: Introductionmentioning
confidence: 99%
“…While there are cases when truly independent committee members take divergent views on the degree of certainty needed to attribute causality of an adverse effect to a single chemical, these divergent views may be more likely where there are multiple chemical exposures. This is because the risk evaluation goes beyond typical single agent evaluations, and methods for combining effects can be challenging [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this continuous exposure, we set the lower ERF threshold (counterfactual level) at 50 µg/m 3 . Lower ERF thresholds are set to reflect threshold effects (if such a threshold exists and is known) and/or a reluctance to extrapolate relationships beyond the range of available data [103]. However, due to the uncertainty in determining a lower ERR threshold for formaldehyde and asthma, we also chose a lower (20 µg/m 3 ) and upper range (60 µg/m 3 ) for which we made sensitivity estimates.…”
Section: Attributable Burden Of Disease Calculations and Analysesmentioning
confidence: 99%